THE APPLICATION OF TSTS MODEL IN CIVIC EDUCATION LESSON IN IMPROVING STUDENTS’ LEARNING ABILITY - Herfina, Hanna (Prodi Teknologi Pendidikan, 2015)
Abstract, The background of this research is the need of various learning method to improve student’s learning ability. One of them is TSTS (two stay to stray). The purpose of this research is to examine TSTS learning method effectiveness in improving student’s learning ability and how much improvement made in implementing TSTS learning method. This research uses cooperative learning with two stay to stray (TSTS) model and action research method trial on learning process of PKn subject at Elementary School. The result of the research indicates improvement on students’ ability on PKn subject by using TSTS learning method, and the effectiveness of this model is proven with the increase of average score of 83.41%. TSTS model in First and Second cycle has proven, exponentially, contributes to the increase of students’ learning results. Keyword: effectiveness, learning method, TSTS model, Elementary School students. Abstrak, Penelitian ini dilatarbelakangi dengan adanya kebutuhan mengenai metode pembelajaran yang bervariasi untuk meningkatkan kemampuan belajar siswa, salah satunya dengan penerapan model pembelajaran TSTS. Adapun tujuan penelitian ini adalah untuk mengetahui efektivitas model pembelajaran TSTS dalam meningkatkan kemampuan belajar Siswa dan seberapa besar peningkatan kemampuan siswa dalam menerapkan model pembelajaran TSTS. Penelitian ini menggunakan konsep cooperative learning dengan model two stay to stray(TSTS), serta metode action research yang diujikan dalam proses belajar mengajar siswa Sekolah Dasar pada materi PKn. Sedangkan untuk hasil yang diperoleh adalah terdapat peningkatan kemampuanSiswa dalam pembelajaran PKn dengan model pembelajaran TSTS dan keefektifan melalui pemanfaatan model pembelajaran TSTS terbukti dengan meningkatnya nilai rata-rata sebesar83,41. Hal itu sudah menandakan bahwa penggunaan model TSTS di dalam siklus I dan II memberikan kontribusi yang sangat besar bagi peningkatan hasil belajar siswa.Kata kunci: efektivitas,metode pembelajaran, model TSTS, siswa SD.